Handling exam stress. (21st March 2019) - Knightsmith, Pooky
Abstract : Exam season is on the horizon and we must help students to handle the pressure if they are to excel.Dr Pooky Knightsmith offers some practical ideas for reducing stress and anxiety in the run up to exams